Geometric Newton-Raphson methods for plane curves - Valasek, Gábor; Horváth, Júlia; Jámbori, András; Sallai, Levente (Acta Cybernetica, 2013)
Our paper reviews Kallay's results on a geometric version of the classic Newton-Raphson method, in the context of plane curve queries, e.g. curve-curve intersection, point-curve distance computation. Variants of the geometric Newton-Raphson methods are proposed and empirically verified.